2010
DOI: 10.1378/chest.09-2697
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Method of Acute Lung Injury Classification for Use in Observational Studies

Abstract: T he diagnoses of acute lung injury (ALI) and its more severe manifestation, ARDS, are based on specifi c clinical and radiographic criteria. 1 The AmericanEuropean Consensus Conference (AECC) standardized these criteria in an effort to improve the systematic identifi cation of patients with this syndrome. This standardization has expedited the recognition of patients with ALI for enrollment into clinical trials and promoted studies on ALI epidemiology by providing a uniform defi nition. [2][3][4][5][6][7] Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…We performed this secondary analysis restricting the control group in an effort to minimize misclassification of borderline cases of ALI as control subjects. Our findings suggest that such misclassification bias exists and could lead to false-negative results in gene association studies of ALI, as has recently been argued by Shah and colleagues (44). We also found that a haplotype containing FAS 21541T and FAS 9325A was associated with development of ALI in the SIRS cohort.…”
Section: Discussionsupporting
confidence: 80%
“…We performed this secondary analysis restricting the control group in an effort to minimize misclassification of borderline cases of ALI as control subjects. Our findings suggest that such misclassification bias exists and could lead to false-negative results in gene association studies of ALI, as has recently been argued by Shah and colleagues (44). We also found that a haplotype containing FAS 21541T and FAS 9325A was associated with development of ALI in the SIRS cohort.…”
Section: Discussionsupporting
confidence: 80%
“…Informed consent was obtained from patients or their proxies. ARDS was defined in accordance with the Berlin definition, with the added requirement of invasive mechanical ventilation over the first 6 days of ICU admission to be confident that the ARDS was attributable to the first septic episode (66,67); chest radiographs were interpreted as described previously (42,68). Acute kidney injury was determined by Acute Kidney Injury Network criteria (69).…”
Section: Methodsmentioning
confidence: 99%
“…To determine independence from our previously reported associations between ABO blood types and ARDS (14), we also conducted analyses stratified by the development of ARDS. ARDS was phenotyped using the Berlin definition and our previously published methods over the first 6 days of ICU admission (37,38). We also conducted analyses within the subgroup of patients who did not receive blood product transfusions during the first 24 hours of enrollment.…”
Section: Statistical Analysesmentioning
confidence: 99%